Evaluation of sanguineous and crystalloid cardioplegic solutions during total heart-lung bypass in dogs - George, R. S.; Jayaprakash, R.; Ramanujam, K.; Radhakrishnan , C.; Archibald, D. (Veterinary Association Malaysia, 2009)
Twenty-four mongrel dogs were subjected to sanguineous and crystalloid cardioplegia for a period of thirty minutes at 20°C and 25°C systemic hypothermia during cardiopulmonary bypass. Cardioplegic solutions were administered at 4°C to induce cardioplegia. Physiological functions of the myocardium revealed that the cardiac function returned to normal sinus rhythm without any loss when blood cardioplegic solution was used at both hypothermic temperatures. The time taken for cardioplegia and cardiac electrical quiescence was achieved earlier at 20°C. Animals in sanguineous cardioplegic group revealed better functional return and revival of cardiac musculature in terms of lesser applications of defibrillator, lesser requirement of inotropic support and early cardiac contraction. This study revealed that sanguineous cardioplegic solution at a systemic temperature of 20°C was found to afford better myocardial protection during an arrest period of 30 minutes.